FOXP 2: A gene for language and speech - Arif, Hakim (Dhaka University Journal of Linguistics, 2010)
Establishing the nature of relationship between Linguistics and bio-sciences, especially Genetic Studies is nether an imagination today, nor an ambitious project at all, as psychologists, linguists and genetic scientists started to put there keen interest in this endeavour at the beginning of the twentieth-first century. The study of FOXP2-a potential human gene responsible for the degeneration of half of the members of famous KE family's speech and language performances, starts an epoch-making initiative in this regard. This paper provides a brief description of the research projects dedicated to explore POXP2 gene, including identifying speech and language behaviour of human beings with particular reference to this gene. Key Words: Grammar gene, language development, autism, SLI, Dyspraxia. DOI: 10.3329/dujl.v2i3.4151 The Dhaka University Journal of Linguistics: Vol.2 No.3 February, 2009 Page: 173-184